Dukungan Sosial dalam Menjaga Kesehatan Mental Remaja Korban Perceraian Orang Tua di MTS Assa`adah Bogor - salwa amaliah; Harmathilda Harmathilda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
This research was conducted at Madrasah Tsanawiyah (Islamic Junior High School) Assa’adah Sukaraja, Bogor, with participants from grades VII–IX who experienced parental divorce. The purpose of this study was to analyze the role of social support in maintaining adolescents’ mental health when facing the psychological impact of parental separation. The research used a descriptive qualitative method with observation, structured interviews, and documentation involving six purposively selected participants. Data validity was ensured through source and method triangulation, while data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing. The results showed that adolescents from divorced families were more vulnerable to feelings of sadness, anxiety, loneliness, and symptoms of depression that affected their social interactions and academic performance. However, social support from peers, teachers, and family played an important role in reducing emotional pressure and enhancing adaptive ability. Support in the form of attention, affection, motivation, and practical assistance strengthened self-confidence and psychological endurance. Thus, social support serves as a protective factor that helps adolescents adjust and maintain their mental health after their parents’ divorce.